DAMPAK LINGKUNGAN PSIKOSOSIAL TERHADAP KESEHATAN MENTAL ANAK DI KABUPATEN ACEH BESAR - Melda Sofia; Herawati Herawati; Kurnia Rahmayanti (JURNAL PENGABDIAN KEPADA MASYARAKAT BIDANG KESEHATAN, 2025)
Child mental health serves as a vital foundation for human resource development in Aceh. This study aims to identify the psychosocial factors that influence the mental health of children in Aceh Besar Regency. Utilizing a descriptive qualitative method, data were collected through observation and secondary literature. The results indicate that religious-cultural parenting styles and community support act as protective factors, yet limited access to professional mental health services remains a primary challenge